Comparing risk of major bleeding between users of different oral anticoagulants in patients with nonvalvular atrial fibrillation. Issue 3 (13th July 2020) - Souverein, Patrick C.; van den Ham, Hendrika A.; Huerta, Consuelo; Merino, Elisa Martín; Montero, Dolores; León‐Muñoz, Luz M.; Schmiedl, Sven; Heeke, Andreas; Rottenkolber, Marietta; Andersen, Morten; Aakjaer, Mia; De Bruin, Marie L.; et al.
Abstract : Aims: The introduction of direct oral anticoagulants (DOACs) has broadened the treatment arsenal for nonvalvular atrial fibrillation, but observational studies on the benefit–risk balance of DOACs compared to vitamin K antagonists (VKAs) are needed. The aim of this study was to characterize the risk of major bleeding in DOAC users using longitudinal data collected from electronic health care databases from 4 different EU‐countries analysed with a common study protocol. Methods: A cohort study was conducted among new users (≥18 years) of DOACs or VKAs with nonvalvular atrial fibrillation using data from the UK, Spain, Germany and Denmark. The incidence of major bleeding events (overall and by bleeding site) was compared between current use of DOACs and VKAs. Cox regression analysis was used to calculate hazard ratios and 95% confidence intervals (CI) and adjust for confounders. Results/Conclusion: Overall, 251 719 patients were included across the 4 study cohorts (mean age ~75 years, % females between 41.3 and 54.3%), with overall hazard ratios of major bleeding risk for DOACs vs VKAs ranging between 0.84 (95% CI: 0.79–0.90) in Denmark and 1.13 (95% CI 1.02–1.25) in the UK. When stratifying according to the bleeding site, risk of gastrointestinal bleeding was increased by 48–67% in dabigatran users and 30–50% for rivaroxaban users compared to VKA users in all data sources except Denmark. Compared to VKAs, apixaban was not associated with an increased risk of gastrointestinal bleeding in all data sources and seemed to be associated with the lowest risk of major bleeding events compared to dabigatran and rivaroxaban.